Simbolni slog v Cankarjevi osebnoizpovedni prozi - Avsenik Nabergoj, Irena (Slavistična revija, 2005)
Based on Cankar's confessional prose and publicistic writing, the article reveals the internal relationship between the author's personal experience, metaphors, and style. By analyzing the development, meaning, and the role of confession and symbols in his works it shows the originality of his literature vis-a vis contemporary European symbolism and his literary role models.
Keywords: Cankar, Ivan, 1876-1918; ironija; literarne študije; moderna; Moderna Therapeutics; simbolika; Slovene literature; slovenska književnost; slovenska proza; stilistika; stylistics